Risk of Symptomatic Intracranial Hemorrhage After Mechanical Thrombectomy in Randomized Clinical Trials: A Systematic Review and Meta-Analysis - Abdullah Reda; Alireza Hasanzadeh; Sherief Ghozy; Hossein Sanjari Moghaddam; Tanin Adl Parvar; Mohsen Motevaselian; Ramanathan Kadirvel; David F. Kallmes; Alejandro Rabinstein (Brain Sciences)
Background: Symptomatic intracranial hemorrhage (sICH) is the most dreaded complication after reperfusion therapy for acute ischemic stroke. We performed a meta-analysis of randomized controlled trials to estimate and compare risks of sICH after mechanical thrombectomy (MT) depending on the location of the large vessel occlusion, concomitant use of intravenous thrombolysis, timing of treatment, and core size. Methods: Randomized controlled trials were included, following a comprehensive search of different databases from inception to 1 March 2024. Random-effect models in a meta-analysis were employed to obtain the pooled risk ratios (RRs) and their corresponding 95% confidence intervals (95% CI) for sICH with MT, and were then compared to other reperfusion treatment regimens, including best medical treatment and intravenous thrombolysis (IVT). Results: MT in the anterior circulation was associated with a significantly higher risk of sICH as compared with no-MT (RR: 1.46; 95%CI: 1.03–2.07; p = 0.037). The risk of sICH was comparable between the MT and MT+IVT groups (RR: 0.77; 95%CI: 0.57–1.03; p = 0.079). There was no difference in sICH risk with MT as compared with no-MT within 6 h of last known well (RR: 1.14; 95%CI: 0.78–1.66; p = 0.485) and beyond that time (RR: 1.29; 95%CI: 0.80–2.08; p = 0.252); the risk of sICH was also comparable between MT conducted within 6 h of last known well and MT conducted beyond that time (p = 0.512). The sICH risk for MT in the posterior circulation (RR: 7.48; 95%CI: 2.27–24.61) was significantly higher than for MT in the anterior circulation (RR: 1.18; 95%CI: 0.90–1.56) (p = 0.003). MT was also associated with a significantly higher sICH risk than no-MT among patients with large core strokes (RR: 1.71; 95%CI: 1.09–2.66, p = 0.018). Conclusions: When evaluating cumulative evidence from randomized controlled trials, the risk of sICH is increased after MT compared with patients not treated with MT. Yet, the difference is largely driven by the greater risk of sICH in patients treated with MT for posterior circulation occlusions and, to a lesser degree, large core strokes. Concomitant use of intravenous thrombolysis and the use of MT in the extended therapeutic window do not raise the risk of sICH.